PERFORMANCE ALLOWANCES IN THE AL-'ADL PERSPECTIVE (STUDY AT THE INDONESIAN MINISTRY OF RELIGION, GOWA REGENCY) - Hikmah Pratiwi Hafid; Salma Said; Wahyuddin Abdullah (JICSA : Journal of Islamic Civilization in Southeast Asian, 2019)
This study discusses the Performance Allowance in the perspective of al-'Adl in the Indonesian Ministry of Religion, Gowa Regency. This type of research is a type of qualitative descriptive study with a phenomelogical approach that explains the phenomena and their meaning for individuals by conducting interviews with a number of individuals and the location of the study was conducted at the Indonesian Ministry of Religion, Gowa Regency. Sources of data obtained consisted of primary data sources of 12 informants, as well as secondary data. Data collection methods used are observation, interviews, and documentation. The results of this study indicate that the process of receiving performance allowances in the manner of payment and giving, addition, and reduction of performance allowances is in accordance with government regulations. In addition, the value of Al-'Adl is an imbalance in the receipt of performance benefits with employee performance which is assessed through employee performance appraisal. The value of Al-'Adl is that there is no equality in providing training opportunities and infrastructure for employees. The value of Al-'Adl is that there is a mismatch in the receipt of performance allowances based on the time of payment, employee workload, and employee obligations.